Prevalence of overweight and obesity associated with the levels of physical fitness among primary school age children in Assiut city - Osama Abdelkarim; Achraf Ammar; Asmaa M.A. Soliman; Anita Hökelmann (SpringerOpen, 2017)
Background: The prevalence of overweight and obesity has increased over the past 30 years to be doubled in children and adolescents and become a major health problem in developing countries. This phenomenon, was often attributed to the engagement in sedentary behaviors and to the lower levels of physical activity. Objectives: To evaluate the prevalence of overweight and obesity among primary school children in Assiut city, aged from 6 to 11 years and its association to the level of physical fitness. Methods: A cross-sectional study was conducted during the period 2014-2015, at 13 governmental primary schools in Assiut city. The sample consisted of 676 children (341boys and 335girls). The data were collected by measuring the anthropometric characteristics including body height, body weight and body mass index and the physical fitness items including endurance, strength, speed, coordination, and flexibility. Results: The prevalence of overweight and obesity was 11.24% and 12.28% respectively. The results of physical fitness data showed significant effects of body anthropometric characteristic in all test items except flexibility with p < 0.001 for both coordination (i.e., balancing backwards) and endurance (6-m-running) tests, p < 0.01 for strength tests, including sit-ups, push-ups and standing long jump and p < 0.05 for 20m sprint test. The body characteristics were correlated with the majority of the physical fitness items. Conclusion: The present study showed a high percent of overweight, obese and skinny subjects among Egyptian children. This abnormal increase or decrease in body weight affects negatively the levels of children's physical fitness. Thus, overweight and obesity should be more attracted by the Egyptian pediatric population with paying attention to the updated health information.